Hedge de crédito através de equity: uma análise empírica com uso de ativos corporativos brasileiros - Leite, Gustavo Ribas de Almeida (2011)
This paper aims to analyze the results of an operation to hedge a diversified credit portfolio through the use of equity. Initially, a reference to the main theoretical aspects of this dissertation with their definitions and literature review will be made. Furthermore, there will be an explanation about the basic parameters of the selection of the sample used and the period during which such protection strategy will be implemented.